PERAN MEDIA DALAM PENDIDIKAN MULTIKULTUR - Rudito, Bambang (Sosio Informa, 2007)
The Role of Massmedia in Multiculture Education. Many people in Indonesia always ask that one culture is a one ethnic group, whereas one ethnic group could insist of many cultures. This condition cause of that many people living in different area, such as in city, periphery, country side, inside the forest, swamp area, beach, and so on. This also we always ask that culture as same as civilization, those definition and meaning are very different, culture is point to abstract value, and civilization is point to behavior, there are pattern for living, such as hunting and gathering, slash and burned cultivation, irrigation cultivation, industrial and modem industry. This article try to explain that how the people in plural society could living together as a nation, and how the mass media could roles as a red yam for uniting people in different culture, ethnic group and civilization.